Public policy making in India - Ayyar, R. V. Vaidyanatha (Delhi, 2009)
Policymaking has two aspects: the technical aspect of developing sound policy proposals, and the entrepreneurial and political aspect of getting policy proposals approved. Policy analysis addresses the first aspect, and policy process and politics, the second, In India, almost all study of policy is limited to the first aspect, while policy process and politics hardly receive any attention in teaching, training or research.
Keywords: Policy making-India